IDENTIFIKASI SIFAT KIMIA PUPUK ORGANIK CAIR JAKABA DARI AKAR PUTRI MALU (Mimosa pudica Linn) - Susanto, Agus; Mustamu, Novilda Elizabeth; Rizal, Khairul; Lestari, Widya (Agros Journal of Agriculture Science, 2024)
JAKABA (Eternal Lucky Mushroom) is a fungus from their  roots of the sensitive plant which used fermentated.  Jakaba can made from the roots cause of this part have Rhizobium bacteria which function as nitrogen fixers. The length of time used to make jakaba liquid organic fertilizer takes twenty-one days after being put in a bucket container. This fungus has the same physical shape as coral but has a fragile texture. The physical changes start from the color which was initially yellowish to brown to become more cloudy, apart from changes in color the changes also include the smell of the LOF produced. This experiment was aim to investigate the growth of jakaba by adding organic material to the sensitive roots of aquatic plants. The benefits of JAKABA liquid organic fertilizer research are to maintain agricultural sustainability by utilizing raw materials that are around. The research was conducted in Tanjung Medan, Bilah Barat, North Sumatra and samples were analyzed at the Socfindo Laboratory and the National Standards Foundation Laboratory, from July 2022 to August 2022. The data was compared with the Organic Fertilizer Quality Standards. The research results show that liquid organic fertilizer from Jakaba has a C/N Ratio of 0.5663 and a pH of 4.66.based on that value that jacab can be recommended as soil amelioration. Key words: Jakaba, POC, Regulation of the Minister of Agriculture, Sensitive plants (Mimosa pudica Linn). INTISARIJAKABA (Jamur Keberuntungan Abadi) adalah jamur yang berasal dari fermentasi akar tanaman sensitif (Mimosa pudica Linn). Bagian yang dapat di manfaatkan sebagai starter untuk pembuatan jakaba adalah akarnya yang memiliki bakteri Rhizobium yang berfungsi sebagai penambat nitrogen, dalm proses produksi jakaba ini membutuhkan durasi yang cukup panjang yaitu dua puluh satu hari setelah di masukan dalam wadah ember. Jamur ini memiliki bentuk fisik yang sama dengan koral namun memiliki tekstur yang rapuh. Adapun perubahan fisik mulai dari warna yang awalnya kekuning kuningan menjadi coklat menjadi lebih keruh, selain perubahan pada warna perubahan juga meliputi bau pada pupuk organik cair yang di hasilkan. Penelitian ini bertujuan untuk mengetahui pertumbuhan jakaba dengan penambahan bahan organik pada akar tanaman peka air. Manfaat penetilian pupuk organik cair JAKABA untuk menjaga pertanian berkelanjutan dengan menggunakan material dasar yang murah dan mudah diperoleh di kawasan penelitian tepatnya di Tanjung Medan, Kecamatan Bilah barat, Labuhanbatu Provinsi Sumatera Utara dan sampel dianalisis di Laboratorium Socfindo dan Laboratorium Landasan Standar Nasional, mulai Juli 2022 hingga Agustus 2022. Hasil penelitian menunjukkan bahwa pupuk organik cair dari Jakaba memiliki C/N Ratio 0,5663 dan pH 4,66, berdasarkan data kimia jakaba diperoleh bahwa jakaba dapat direkomendasikan sebagai bahan pembenah tanah. Kata kunci : Jakaba, POC, Peraturan Menteri Pertanian, Tanaman peka (Mimosa pudica Linn).